ISOLASI DAN IDENTIFIKASI SENYAWA TERPENOID YANG AKTIF ANTIBAKTERI PADA HERBA MENIRAN (Phyllanthus niruri Linn) - I W. G. Gunawan; I G. A. Gede Bawa; N. L. Sutrisnayanti (Jurnal Kimia (Journal of Chemistry), 2008)
Isolation and identification of terpenoid, antibacterial compounds meniran herb (Phyllanthus niruri Linn) by GasChromatography – Mass Spectroscophy were carried out. Two kinds of extraction, i.e. maseration using methanoland the sochlet using n-hexane were employed.The extract obtained were contains terpenoids basedon fitochemical test of Liberman-Burchard n-hexaneextract was tested for antimicrobial activity against Escherichia coli ATCC® 25292 and Staphylococcus aureusATCC® 25293. In this study we obtained that n-hexane extract by sochlet extraction showed greater activitycompared to the extract by maseration with methanol, as indiated by disc diameter of inhibition zone. Diametricinhibition zone for these two extract are 1 mm for Escherichia coli and 0,5 mm for Staphylococcus aureus, formethanol extract, and where are 10 mm for Escherichia coli and 12 mm for Staphylococcus aureus for n-hexaneextract.The n-hexane extract was then purified using column chromatography. The pure extract was analyzed usingGas Chromatography - Mass Spectroscophy. Gas Chromatography - Mass Spectroscophy data indicated that theextract contains two compounds, i.e. phytadiene [ M+ ] 278 and 1,2 seco – cladiellan m/z 335 [ M+ - H ].